2005
DOI: 10.3748/wjg.v11.i21.3175
|View full text |Cite
|
Sign up to set email alerts
|

Kimchi and soybean pastes are risk factors of gastric cancer

Abstract: AIM: This case-control study investigated the effects of kimchi, soybean paste, fresh vegetables, nonfermented alliums, nonfermented seafood, nonfermented soybean foods, and the genetic polymorphisms of some metabolic enzymes on the risk of gastric cancer in Koreans. METHODS:We studied 421 gastric cancer patients and 632 age-and sex-matched controls. Subjects completed a structured questionnaire regarding their food intake pattern. Polymorphisms of cytochrome P450 1A1 (CYP1A1), cytochrome P450 2E1 (CYP2E1), gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 46 publications
1
53
1
Order By: Relevance
“…SNPs of CYP1A1 termed as m1 (at 1,188 bp 3 ¶ of the stop codon) and m2 (I462V) have been often found associated with risk in several smoking-related tumors (3). Only two case control studies have reported results for gastric cancer in relation with m2 mutation: one in Korea observed a weak but significant 34% increase in risk (17), whereas no association was found in a study in Japan (18). We observed a tendency to decreased risk for both m1 (significant among smokers) and m2 mutations.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…SNPs of CYP1A1 termed as m1 (at 1,188 bp 3 ¶ of the stop codon) and m2 (I462V) have been often found associated with risk in several smoking-related tumors (3). Only two case control studies have reported results for gastric cancer in relation with m2 mutation: one in Korea observed a weak but significant 34% increase in risk (17), whereas no association was found in a study in Japan (18). We observed a tendency to decreased risk for both m1 (significant among smokers) and m2 mutations.…”
Section: Discussioncontrasting
confidence: 58%
“…Deletion of GSTT1 was found not to be associated with gastric cancer risk in several studies in a variety of populations (17,(20)(21)(22)(23)(24)(25)(26)(27). One study in Poland found a significant increase in risk for null GSTT1 limited to cases with age <50 years (28); another study in China reported a significant OR of 2.5 for GSTT1 deletion (29).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 39 articles that report on the effects of GSTT1 polymorphisms on gastric cancer in Asia covering in total of 7,737 gastric cancer cases and 10,823 controls were remained for data extraction. 11 of them were Chinese (Qian et al, 2001; Sheng and Wang, 2002;Zheng et al, 2002;Liu et al, 2003;Ye et al, 2003;Zhang et al, 2003;Zhou et al, 2003;Xie et al, 2008; Feng et al, 2010; Liu et al, 2013;Shi et al, 2014), and 28 were English (Katoh et al, 1996;Setiawan et al, 2000; Cai et al, 2001;Saadat and Saadat, 2001; Gao et al, 2002a;Wu et al, 2002; Choi et al, 2003;Roth et al, 2004;Mu et al, 2005;Nan et al, 2005a; Sheng et al, 2005;Tamer et al, 2005; Hong et al, 2006; Al-Moundhri et al, 2009;Malik et al, 2009;Masoudi et al, 2009;Moy et al, 2009;Piao et al, 2009;Nguyen et al, 2010;Yadav et al, 2010;Luo et al, 2011;Tripathi et al, 2011;Yadav et al, 2011;Zhang et al, 2011; Jing et al, 2012;Malakar et al, 2012; Eom et al, 2013; Haholu et al, 2013). The characteristics of included studies were summarized in Table 1.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
“…In epidemiologic studies, the health benefits of soy for gastric cancer are inconsistent: some studies reported that soy products, such as bean and tofu, significantly decrease the risk of gastric cancer (4,5,13), whereas other studies reported that soy products were not significantly associated with a decreased risk of gastric cancer (14)(15)(16)(17). The inconsistency for dietary intake might be due to the use of food frequency questionnaires and the case-control design.…”
Section: Introductionmentioning
confidence: 99%